Evaluation of Teacher Professional Training (TPT) program in the position of full online learning - Salamah, Ummu; Istiyono, Edi (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2022)
The purpose of this study is to evaluate the Teacher Professional Training program (TPT) in first force Makassar State University (UNM) in a science study program in fully online learning. This research is an evaluation research with the CIPP model from Stufflebeam. The data were collected using a questionnaire-based survey method with descriptive statistical analysis. The instrument was distributed via google form to TPT students in positions. The conclusions of the research results are as follows: (1) The context aspect shows that the TPT program helps develop teacher professionalism (2) The input aspect shows that the Educational Personnel Education Institute organizers have good quality in implementing the TPT program (3) The process aspect shows that there is a relevance between the knowledge test material and the performance test on the educational competence and professionalism of teachers. (4) The product aspect shows that the TPT program affects changes in teacher teaching methods even though it is carried out entirely online.